Proceso contable de la Empresa Solution Coorporation Patgior S.A.S. en la ciudad de Babahoyo periodo 2022. - Vera Aspiazu, Alfonsina Zaida (2024)
The case study deals with the topic of the accounting process in the company Solution Coorporation Patgior S.A.S, in the period 2022, due to the fact that it presents weaknesses related to an inadequate accounting process such as the absence of necessary procedures to carry out an adequate record of daily transactions. For this reason, the objective of the work is to analyze the accounting process of the company in the year in the period described. The methodology used consisted of a qualitative approach, types of documentary and descriptive research, inductive and analytical-synthetic methods, as well as interview techniques and direct observation with their respective instruments. The results were that the company does not have formal policies to archive accounting documentation, it makes backup copies, but they are not stored in a safe place, likewise, there are no internal control activities over the business archive to identify weaknesses. The organization does not have an orderly record of files and backup copies, among other results. In conclusion, Solution Coorporation Patgior S.A.S does not efficiently manage the documentation by not storing it in a reliable site and does not establish policies and processes for the correct filing of accounting data. The main weaknesses of the accounting process are based on the fact that the company has technological tools to develop an automated accounting process, but they only use it for billing and inventory control, and no training is carried out to increase the level of knowledge about accounting regulations.